Ethnic differences in the prevalence of knee pain among adults of a community in a cross-sectional study. Issue 12 (1st December 2016) - Chia, Yook Chin; Beh, Hooi Chin; Ng, Chirk Jenn; Teng, Cheong Lieng; Hanafi, Nik Sherina; Choo, Wan Yuen; Ching, Siew Mooi
Abstract : Objective: To determine the prevalence of knee pain among 3 major ethnic groups in Malaysia. By identifying high-risk groups, preventive measures can be targeted at these populations. Design and setting: A cross-sectional survey was carried out in rural and urban areas in a state in Malaysia. Secondary schools were randomly selected and used as sampling units. Participants: Adults aged ≥18 years old were invited to answer a self-administered questionnaire on pain experienced over the previous 6 months. Out of 9300 questionnaires distributed, 5206 were returned and 150 participants who did not fall into the 3 ethnic groups were excluded, yielding a total of 5056 questionnaires for analysis. 58.2% (n=2926) were women. 50% (n=2512) were Malays, 41.4% (n=2079) were Chinese and 8.6% (n=434) were Indians. Results: 21.1% (n=1069) had knee pain during the previous 6 months. More Indians (31.8%) experienced knee pain compared with Malays (24.3%) and Chinese (15%) (p<0.001). The odds of Indian women reporting knee pain was twofold higher compared with Malay women. There was a rising trend in the prevalence of knee pain with increasing age (p<0.001). The association between age and knee pain appeared to be stronger in women than men. 68.1% of Indians used analgesia for knee pain while 75.4% of Malays and 52.1% of Chinese did so (p<0.001). The most common analgesic used for knee pain across all groups was topical medicated oil (43.7%). Conclusions: The prevalence of knee pain in adults was more common in Indian women and older women age groups and Chinese men had the lowest prevalence of knee pain. Further studies should investigate the reasons for these differences.